Teratoma retroperitoneal en niños: revisión del tema a propósito de un caso (2014)
ABSTRACT: Retroperitoneal teratomas constitute 3% of all pediatric tumors. However, no information is available in Colombia to support this frequency, and there is no consensus on the diagnosis, management and prognosis of this tumor. We report a case in a newborn girl in Bucaramanga, Colombia, diagnosed by means of imaginological studies and treated by surgery. We review the literature, considering general aspects, differential diagnosis, histological features and management, in order to guide physicians to consider this diagnostic possibility.